DEMOKRASI DALAM PERSPEKTIF AL-QUR’AN: METODE MAUDHU’I - Muhammad Dzulfahmi Al-haqiqi; Muhammad Ridho Fathoni; Muhamad Rizal Taufiq (Jurnal Penelitian Multidisiplin Ilmu, 2023)
This research is descriptive research using the maudhu'i interpretation approach to find out the verses about democracy and the views of Muslims regarding democracy, especially those who absolutely disbelieve and democracy in Islamic views. Based on the data obtained, it is found that democracy means power in the hands of the people or government by and for the majority. Democracy contains two important elements, namely freedom or liberty, and equality. In the Qur'an, democracy is referred to as ?????? as in the following verse: Q.S Ali - Imran:159, Q.S Ash-syuro: 38, and Q.S Al-Baqarah: 233. the Muslim view of democracy is threefold: The first view, Ali Ghufran alias mukhlas overall assessment that democracy and its leadership is absolutely kafue. The second view, which sees democracy as not entirely kufr and may utilize it on the condition that it does not contradict Shari'a. The third view, which sees democracy as permissible in all circumstances, by following the majority vote regardless of whether or not it contradicts shari'ah. It can be concluded that entering the political area that is developing today needs to be done to realize the ideals of upholding Islamic law, with consideration of changing the secular siyasah system towards Islamic siyasah. Although democracy presupposes the election of a policy maker based on a majority vote, but only in this way can the system be changed, so participating in elections may be obligatory. Islam has regulated democracy in a structured manner through the laws laid down in the Qur'an. The author uses commentaries from various books and sources to broadly describe democracy in the view of Islam.